(untitled) (Research, Society and Development, 2022)
The study aimed to carry out a narrative literature review on the hospital discharge process of people with stroke. The search was performed in the databases, PubMed and Academic Google, between July and August 2021. The descriptors used were: “Stroke”, “discharge planning” OR “Transitional Care” AND “Caregivers”. As an inclusion criterion, publications that addressed the topic, published between the years 2016 to 2021, written in Portuguese or English and with online access, were considered. The pre-selection considered the reading of the title and abstract of the publications and classified at the end 11 for full reading. As main results, it was found that the professional most involved in the hospital discharge process of patients affected by stroke is the nurse. However, there seem to be difficulties in the care transition process, especially with regard to communication and involvement of patients and caregivers in decision-making. Discharge planning represents an essential strategy for transferring the patient from the hospital to the home and can contribute to the reduction of: readmission rates, complications, length of hospital stay, care costs and mortality. Still, the importance of health education and interprofessional work for the comprehensive care of people with stroke is highlighted.